2020
DOI: 10.1108/et-04-2020-0096
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting entrepreneurial intentions among university students in Saudi Arabia: testing an integrated model of TPB and EO

Abstract: PurposeThis research intends to contribute to the literature of entrepreneurial intentions through determining the factors impacting the entrepreneurial intentions among students in different academic programs. This is in order to enhance and improve entrepreneurship-related procedures within relevant universities.Design/methodology/approachThe study was conducted by a structured survey questionnaire on 261 students in the University of Hail. The questionnaire was developed based on previous studies. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
83
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 55 publications
17
83
3
5
Order By: Relevance
“…For instance, the support from peers and family can help to enhance individual attitude. Previous studies have also integrated TPB with entrepreneurship in the context of youth studies (e.g., Al-Mamary et al, 2020;Ridha, & Wahyu, 2017). Sharahiley (2020) for instance has found that innovativeness emerged as the strongest predictor of entrepreneurial intention and behaviour.…”
Section: Ajzen's Theory Of Planned Behaviourmentioning
confidence: 99%
“…For instance, the support from peers and family can help to enhance individual attitude. Previous studies have also integrated TPB with entrepreneurship in the context of youth studies (e.g., Al-Mamary et al, 2020;Ridha, & Wahyu, 2017). Sharahiley (2020) for instance has found that innovativeness emerged as the strongest predictor of entrepreneurial intention and behaviour.…”
Section: Ajzen's Theory Of Planned Behaviourmentioning
confidence: 99%
“…Subjective norms contribute to perceived social impact to involve or not to involve in entrepreneurship, while perceived behavior control is the ease or difficulty that an individual to a career as an entrepreneur (Entrialgo & Iglesias, 2016). While TRA notes that intention is often assumed to portrait the motivational dimensions which drive individual willingness or behavior (Al-Mamary et al, 2020;Koe et al, 2015). This theory believes that attitudes and subjective norms can explain intention.…”
Section: Underpinnings Theorymentioning
confidence: 99%
“…Entrepreneurial orientation is an attractive research issue, especially regarding the business output (Covin & Wales, 2019, Al-Mamary et al, 2020a, Al-Mamary et al, 2020b. Execution, procedures and decision-making exercises are described to provide a guide for new and emerging enterprises (Rauch et al, 2009).…”
Section: Entrepreneurial Orientation (Eo)mentioning
confidence: 99%